ARTIFICIAL INTELLIGENCE AND ACCOUNTANTS’ WORK EFFICIENCY: A GLOBAL BIBLIOMETRIC AND SCIENCE-MAPPING ANALYSIS OF ACCOUNTING RESEARCH - Noldin Jerry Tumbel (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: This study maps the intellectual, conceptual, and temporal structure of research on artificial intelligence (AI) and accountants’ work efficiency. Design/methodology/approach — A Scopus search identified 1,418 English-language, open-access journal articles published from 2020 to 2026. Because the term “account” generated finance- and banking-related noise, title and author-keyword screening retained 185 accounting- and audit-relevant articles. Performance analysis was combined with keyword co-occurrence, network, overlay, and density mapping using VOSviewer-compatible files. Findings — Annual output increased from 3 articles in 2020 to 67 in 2025, with 39 additional articles indexed during the partial 2026 period. The corpus comprised 91 sources and 520 authors, with a mean of 14.0 citations per article and a median of 3. The keyword network contained 35 terms, 70 links, and five clusters covering audit and risk analytics; professional automation and ethics; generative AI, financial reporting, and governance; digital infrastructure; and education and technology acceptance. The thematic focus shifted from RPA, blockchain, and IoT toward generative AI, large language models, explainable AI, corporate governance, and financial reporting. Originality/value — This study provides an outcome-centered and reproducible map of AI-enabled accounting efficiency, distinguishes established automation themes from emerging generative-AI and governance research, and documents the screening required to address query contamination. Keywords: artificial intelligence; accounting; work efficiency; bibliometric analysis; science mapping.   Abstrak: Studi ini memetakan struktur intelektual, konseptual, dan temporal dari penelitian mengenai kecerdasan buatan (AI) dan efisiensi kerja akuntan. Desain/metodologi/pendekatan — Pencarian di Scopus mengidentifikasi 1.418 artikel jurnal akses terbuka berbahasa Inggris yang diterbitkan antara tahun 2020 dan 2026. Karena istilah "account" menghasilkan data yang tidak relevan (noise) terkait keuangan dan perbankan, penyaringan berdasarkan judul dan kata kunci penulis menyisakan 185 artikel yang relevan dengan bidang akuntansi dan audit. Analisis kinerja digabungkan dengan pemetaan ko-okurensi kata kunci, jaringan, overlay, dan kepadatan menggunakan berkas yang kompatibel dengan VOSviewer. Temuan — Jumlah publikasi tahunan meningkat dari 3 artikel pada tahun 2020 menjadi 67 artikel pada tahun 2025, dengan tambahan 39 artikel terindeks selama periode parsial tahun 2026. Korpus data mencakup 91 sumber dan 520 penulis, dengan rata-rata 14,0 sitasi per artikel dan nilai tengah (median) sebesar 3. Jaringan kata kunci memuat 35 istilah, 70 tautan, dan lima klaster yang mencakup analitik audit dan risiko; otomatisasi profesional dan etika; AI generatif, pelaporan keuangan, dan tata kelola; infrastruktur digital; serta pendidikan dan penerimaan teknologi. Fokus tematik bergeser dari RPA, blockchain, dan IoT menuju AI generatif, model bahasa besar (LLM), AI yang dapat dijelaskan (explainable AI), tata kelola perusahaan, dan pelaporan keuangan. Orisinalitas/nilai — Studi ini menyajikan peta efisiensi akuntansi berbasis AI yang berorientasi pada hasil dan dapat direplikasi, membedakan tema otomatisasi yang sudah mapan dari penelitian baru mengenai AI generatif dan tata kelola, serta mendokumentasikan proses penyaringan yang diperlukan untuk mengatasi kontaminasi hasil pencarian. Kata kunci: kecerdasan buatan; akuntansi; efisiensi kerja; analisis bibliometrik; pemetaan sains.